Intra-System Shift Found in Borobudur Temple Tourism Brochure: A Translation Study - Suarliem, Valencia Friska; Maharani, Ida Ayu Putu Chintya; Sukarsih, Ni Nyoman Tri (LITERA : Jurnal Bahasa Dan Sastra, 2024)
In translation, Intra-system shift is a translation process where a formally corresponding term in the source language (SL) loses its correspondence in the target language (TL). This study aims to analyze the intra-system shift from Indonesian as a source language into English as a target language of translation used in Borobudur Temple tourism brochure. It used a descriptive-qualitative method, which displayed the data with words in descriptive form. The data were taken from Borobudur Temple tourism brochure Indonesian-English translation. The data is then collected by using observation, documentation and note-taking methods. The data was analyzed by doing data reduction, data display, and drawing conclusion. The result shows that intra-system shift is indeed found in the Candi Borobudur Indonesian-English translation. From the five marks in intra-system shift , three marks were found in the brochure.